The behaviour of purchasing smuggled cigarettes in Taiwan - Tsai, Y (BMJ Group, 2003)
Objective: Since market liberalisation in 1987, the Taiwan Tobacco and Wine Monopoly Bureau (TTWMB) annual statistics indicate that both the demand for imported cigarettes as well as the number of seized smuggled packs have increased with an average revenue loss of NT$4942 million over the past 15 years. The NT$10 average increase in cigarette prices after Taiwan entered the World Trade Organization (WTO) and the implementation of the Tobacco and Alcohol Tax Law in 2002 are forcing policy makers to examine smuggling even more closely. This study evaluates factors that affect an individual smoker's decision to purchase smuggled cigarettes, particularly when faced with higher prices. Design: 437 male smokers of imported cigarettes were drawn from a national interview survey on cigarette consumption, which the Division of Health Policy Research at the National Health Research Institutes conducted during the year 2000. Multiple logistic regression models were used to analyse the behaviour of purchasing smuggled cigarettes with respect to demographic factors, economic factors, smoking behaviour, and other variables. Results: Cigarette price was the driving factor most closely linked to the purchase of smuggled cigarettes—a 1% increase in cigarette price raised the likelihood of purchasing smuggled cigarettes at least 2.60 times (95% confidence interval (CI) 1.08 to 6.26). Smokers who spent more than NT$1000/month on cigarettes were twice as likely to purchase smuggled cigarettes as those who spent less than NT$1000 (odds ratio (OR) 2.34, 95% CI 1.48 to 3.70). Betel nut chewers were more likely to purchase smuggled cigarettes (OR 1.80, 95% CI 1.09 to 2.90). Smokers who opposed cigarette taxation policy were 1.69 times more likely to buy smuggled cigarettes. Personal income was not significantly associated with smuggled cigarettes purchases. Conclusions: This study evaluates what causes smokers to purchase smuggled cigarettes. We have determined that cigarette price is the most important factor and that betel nut vendors are the main suppliers. Our study provides policy makers with information that can help them develop effective strategies to curb cigarette smuggling after Taiwan's recent cigarette tax reform, which has increased cigarette prices.